TUJUAN DAN MANFAAT PENELITIAN DALAM PENELITIAN HUKUM KELUARGA - Alkaizha Nuran Hakiki; Mohamad Sar’an; Syahrul Anwar (JURNAL ILMIAH NUSANTARA, 2026)
This article highlights the close relationship between research objectives and the formulation of the research problem. Research objectives, which specify the focus and intended outcomes of a study, should be directly derived from the research questions. When these two components are not aligned, readers may struggle to recognize the significance, purpose, and relevance of the study. Moreover, research objectives translate the abstract ideas presented in the research problem into concrete and measurable aims. They provide a practical framework for designing the study, selecting appropriate research methods, analyzing data, and interpreting the findings in the final report. Therefore, research objectives should be formulated only after the research problem has been clearly identified and appropriately delimited, as these stages establish the foundation for defining the objectives. The complexity of the objectives also depends on the nature and complexity of the research problem itself. In addition, the article emphasizes the importance of explaining the benefits of the research in the introductory section. This discussion should demonstrate how the findings may be applied and contribute to various stakeholders, including academic institutions and the broader community. Consequently, well-defined research objectives and a clear explanation of the study's potential benefits are fundamental to producing focused, meaningful, and impactful research.